Pengaruh Zakat Perbankan Dan Corporate Social Responsibility Terhadap Kinerja Bank Umum Syariah - Anriani, Gusti; Siregar, Fatahuddin Aziz; Amidy, Rizal Ma'ruf (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Padangsidimpuan, 2020)
The percentage of funds issued by banks for zakat and Corporate Social Responsibility (CSR) is not the same every year. This can be seen from the expenditures of several banks each year in the 2013-2015 period. As with zakat and CSR, bank income is unstable every year, this is also evident from several banks that experienced an increase and decrease during the 2013-2015 period. The research objective in this study was to determine whether there is an effect of banking zakat and corporate social responsibility on the performance of Islamic commercial banks in Indonesia for the 2013-2015 period. This research is a quantitative research, the data source comes from secondary data in the form of time series data + cross-section as many as 9 samples. The data analysis technique used regression estimation method, with t test and F test. The data processing used Eviews9 computer program. The results of the research partially (t test) for the bank Zakat variable did not have a significant effect on bank performance, while the CSR variable partially had a significant effect on bank performance. Meanwhile, simultaneously the Zakat and CSR variables have a significant effect on bank performance. Keywords: Zakat, Corporate Social Responsibility, Banking Performance.